Self-Destructive Work Behavior Management for Socio-Economic Emancipation: A Classic Case of Saving One from Oneself - Ugwuzor, Miebi (Journal of Economics and Behavioral Studies, 2021)
Africa is amply endowed with diverse dimensions of resources as well as having a rich cultural heritage with great potentials for economic growth and development. It is also worthy of mention that the resourceful capacities of Africans in the diaspora in all spheres of life have contributed immensely to the development of other continents of the world. Despite these great progressive potentials, a large percentage of African States are in obvious and dire need of sustainable socio-economic emancipation. This glaring need to identify the key challenges and propose solutions necessitated this study. This study is conceptual and examined self-destructive behaviors at multiple levels using theoretical underpinnings from the Human survival and the self-destruction paradox as well as the dialectical behavioral therapy. This Paper identified several ingrained sources of self-destructive work behaviors in contemporary public sector workplaces in Africa which contribute to the socio-economic challenges. This work highlights that these obnoxious, self–destructive work behaviors seem highly inimical to management praxis. The behaviors seem capable of contending against the aggregate fight for sustainable socio-economic emancipation of the Continent. Deliberate self-salvation was opined here to steer away behaviors, especially in workplaces, from this current path of self-destruction. Novel Actionable thoughts were suggested to stem this unfavorable tide and push for a generation of operational work behaviors as well as an ethical renaissance in management praxis for the emergence of archetypes completely devoid of any anti-progress tendencies.